To Google Translate™ or not? Newcomer Latino communities in the middle. Issue 2 (15th March 2018) - Rodríguez-Castro, Mónica; Salas, Spencer; Benson, Tracey
Abstract: LaRocque, Kleiman, and Darling (2011) characterized parental involvement as the "missing link" in school achievement. For this reason, especially, middle grades teachers and teacher leaders want very much to reach out to newcomer Latino families—and they do. Although Google Translate ™ has emerged as a go-to tool for many teachers and administrators, sometimes machine-translation backfires. In this article, we leverage a series of vignettes to illustrate the hazards of Spanish/English pseudotranslation. We continue with a brief presentation of the PROSE checklist as a deliberate strategy for increasing the readability of school-to-home communication for all students—and its potential applications for framing communication using translation software. Our intent is grounded in the notion that middle school advocacy is not limited to teacher-student interactions. Rather, in the shifting demographics of middle school education, leadership must also include focused, thoughtful, responsive, and accessible communication with immigrant newcomer families (Allen, 2007; Delgado-Gaitan, 2001, 2004; López, Scribner, & Mahitivanichcha, 2001).